Academic Clinic Development Strategy Through Balanced Scorecard Approach (Study at RSGM-P FKG Usakti Academic Clinic, Indonesia) - Rosmalinda Suryani; Joko Kusnoto; Asyurati Asia (Universitas Muhammadiyah Yogyakarta, 2024)
The Academic Clinic is a supporting facility for the academic continuity of dental faculty students. The need for the preparation of a strategic plan for the development of academic clinic services as a health organization aims to anticipate various kinds of situations that are always changing and related to external and internal environmental factors. Strategic management tools can help generate some of the best alternative strategies for developing academic clinics with the Balanced Scorecard (BSC) approach. This study aims to develop a development strategy for the Dental and Oral Educational Hospital Faculty of Dentistry Universitas Trisakti (RSGM-P FKG Usakti) Academic Clinic based on four BSC perspectives: finance, customers, internal business processes, and learning and growth. This operational research was conducted using quantitative and qualitative methods. Secondary data was collected from Badan Pusat Statistik (BPS), Hospital Annual Report, and comparable RSGMs. Primary data collection used questionnaires, interviews, and a Consensus Decision Making Group (CDMG) to obtain variables that became strategic factors. Based on four BSC perspectives, it increases academic clinic income from financial perspectives, provides easy access and increases customer trust for customer perspectives, captures market opportunities, builds a good image of academic clinics from an internal business processes perspective, and increases human resource capabilities for learning and growth perspective.